2005
DOI: 10.1002/jsfa.2360
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of natural dyes for textile dyeing from coloured plant wastes released from the food and beverage industry

Abstract: The food and beverage industry releases considerable amounts of wastes which contain natural dyes. Such wastes could serve as a sources for the extraction of natural dyes for textile-dyeing operations. The extraction of brilliant yellow and red colours from fruits and vegetables is of particular interest. Wastes, e.g. pressed berries, pressed grapes, distillation residues from strong liquor production, and wastes and peels from vegetable processing, have been extracted with boiling water and test dyeings on wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
73
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(82 citation statements)
references
References 7 publications
(6 reference statements)
0
73
0
5
Order By: Relevance
“…corymbosa. The light fastness grade 2 or 3 was required as the lowest limit for positive selection; however, values of light fastness could be increased by further investigations to exceed the limit of grade 2-3 (Bechtold et al 2006). Our results showed that light fastness grade were 3 and 3/4 for I. tinctoria and 3 for I. candolleana while 2/3 for I. tinctoria subsp.…”
Section: Fastness Propertiesmentioning
confidence: 61%
See 1 more Smart Citation
“…corymbosa. The light fastness grade 2 or 3 was required as the lowest limit for positive selection; however, values of light fastness could be increased by further investigations to exceed the limit of grade 2-3 (Bechtold et al 2006). Our results showed that light fastness grade were 3 and 3/4 for I. tinctoria and 3 for I. candolleana while 2/3 for I. tinctoria subsp.…”
Section: Fastness Propertiesmentioning
confidence: 61%
“…Poor or insufficient washing fastness could be identified as a limitation for the use of natural dyes extracted from the different representative sources. Sufficient dyestuff fixation also can be seen as a good mark for washing fastness bleeding (Bechtold et al 2006). The dry rubbing fastness ranged in 3/4 to 4 for I. tinctoria and I. candolleana; 4/5 for I. tinctoria subsp.…”
Section: Fastness Propertiesmentioning
confidence: 99%
“…Ancak sentetik boyarmaddelerin elde edilmesiyle birlikte önemini çok büyük oranda kaybetmiştir [6]. Gelecek ile ilgili yeni stratejiler, sürdürülebilir prosesler ve çevre duyarlılığı gibi nedenler doğal boyarmaddelerin yeniden gündeme gelmesine önemli ölçüde neden olmuştur [7]. Günümüzde doğal boyarmaddeler de bu açıdan toplumun ve bilim insanlarının ilgisini önemli ölçüde çekmektedir.…”
Section: Introductionunclassified
“…Söz konusu çalışmalarda vurgulanan ana fikir, bitkisel atıkların önemli miktarda doğal boya içerdiği, bu tür atıkların tekstil boyamacılığında kullanılacak boyarmaddeler için kaynak olarak kullanılabileceğidir [8][9][10][11][12][13]. Bechtold vd.…”
Section: Introductionunclassified
“…Boyama işleminde elde edilen boyarmadde çözeltileri-nin yün, pamuk, keten, poliamid 6,6 liflerine bağlanma performansları incelenmiştir. Farklı boyama sıcaklıkları ve mordanlama metod ve mordan miktarları kullanılarak boyama prosedürünün optimizasyonu hedeflenmiştir [8][9][10][11][12][13].…”
Section: Introductionunclassified